Capillary convection in pulsed – butt welding of miscible dissimilar couple. (July 2017) - Hu, Yaowu; He, Xiuli; Yu, Gang; Zhao, Shusen
Pulsed laser butt welding of miscible dissimilar couple has been studied numerically based on a three-dimensional heat and mass transfer model. Driving forces of molten metal flow in the case of stainless steel and nickel are compared using dimensional analysis. Thermo-capillary convection due to surface temperature gradient is recognized as the dominating fluid flow. Temperature coefficients of surface tensions are varied to investigate the influences of the convection on heat and mass transfer phenomena in weld pool. The temperature fields at stainless steel and nickel sides are found to be asymmetric and are greatly affected by different Marangoni convections. Concentration of Ni increases as the temperature coefficient of surface tensions changes from negative to positive. The temperature coefficient of surface tension of stainless steel has greater impact on the weld pool configuration and element concentration than that of nickel. The obtained weld pool configurations are found to be dependent on Prandtl number and convection patterns.